Handgrip Strength Adds More Prognostic Value to the Model for End‐Stage Liver Disease Score Than Imaging‐Based Measures of Muscle Mass in Men With Cirrhosis. Issue 10 (18th August 2019) - Sinclair, Marie; Chapman, Brooke; Hoermann, Rudolf; Angus, Peter W.; Testro, Adam; Scodellaro, Thomas; Gow, Paul J.
Abstract : Sarcopenia is associated with mortality in cirrhosis, but there is no gold standard for its diagnosis. The comparative utility of different diagnostic methods is unknown. This single‐center observational cohort study followed 145 men referred for liver transplant evaluation between 2005 and 2012. Muscle mass was estimated by handgrip strength, dual energy X‐ray absorptiometry (DEXA) lean mass, and single‐slice computed tomography (CT) scan at the fourth lumbar vertebra. Recorded outcomes included time to death or liver transplantation. The median (interquartile range [IQR]) age was 54 years (47‐59 years), and Model for End‐Stage Liver Disease (MELD) score was 17 (14‐23). Of 145 men, 56 died with a median (IQR) time to death of 7.44 months (3.48‐14.16 months). In total, 79 men underwent transplantation with median (IQR) time to transplant of 7.20 months (3.96‐12.84 months). The prevalence of sarcopenia differed between diagnostic modalities with 70.3% using CT muscle mass, 45.9% using handgrip strength, and 38.7% using DEXA. Muscle mass was inversely associated with wait‐list mortality for measured CT muscle mass (hazard ratio [HR], 0.94; 95% confidence interval (CI), 0.90‐0.98; P = 0.002), DEXA muscle mass (HR, 0.99; 95% CI, 0.99‐0.99; P = 0.003), and handgrip strength (HR, 0.94; 95% CI, 0.91‐0.98; P = 0.002). These results retained significance independent of the MELD score. In predicting mortality, the MELD–handgrip strength bivariate Cox model was superior to a MELD‐CT muscle Cox model ( P < 0.001). In conclusion, handgrip strength combined with MELD score was the superior predictive model in this novel study examining 3 commonly employed techniques to diagnose sarcopenia in cirrhosis. Handgrip strength has additional potential clinical benefits because it can be performed serially without the radiation dose, cost, and access issues attributable to CT and DEXA.